Kondisi Lahan Dusung Sagu Dalam Pelestarian Sempadan Sungai-Pantai di Kawasan Wai Poka Kota Ambon - Irfan Alexander Wakum; Conradus Ufie; Simson Liubana (JURNAL PERTANIAN KEPULAUAN, 2023)
The research aims was to know land condition of dusung sago around the river riparian area or at least 10 meters from the right and/or left of the riverbank. The method used was a survey with free survey observation distance approach. The observation was conducted intensively on sample area of dusung sago located around 10 meters from the riverbank. The result showed that the soils found in the research area are alluvial and regosol soils according to the National Soil Classification (2014), and their formation are influenced by very poor to poor hydrological condition as indicated by very shallow average groundwater at < 20 cm below ground level. The existence of sago plants in the Wai Poka riparian area is endangered by the expansion of settlements in the Poka area.